Performances of MnO2 and SnO2 Coated MnO2 as Cathode Materials for Aqueous Rechargeable Zinc-ion Batteries (Journal of Science and Technology Research, 2024)
In this study, the micro-emulsion method was used to create the manganese-based cathode materials MnO2 and MnO2@SnO2. For the use as cathode materials in rechargeable zinc-ion batteries, MnO2 and SnO2 coated MnO2@SnO2 were synthesized. FT-IR, Powder X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDS), and UV-visible Spectroscopy were used to characterize the as-prepared materials. Electrochemical impedance spectroscopy (EIS), battery charge-discharge (BCD), and cyclic voltammetry (CV) techniques were used to investigate the electrochemical properties of the prepared cathode materials for aqueous rechargeable zinc-ion batteries (ARZIBs). The CV profiles were measured in the potential range of 2.1-1.0 V at a scan rate of 20 mV/s. A pair of redox peaks can be seen in the cycle of CV curves. Charge/discharge cycles of SnO2 coated MnO2@SnO2 electrodes are higher than those of pristine MnO2. SnO2 coated MnO2@SnO2 electrodes have better initial charge/discharge capacities than pristine MnO2 electrodes, which is a factor to take into account. In the first cycle, SnO2 coated MnO2@SnO2 electrode has a 26% higher charge capacity than the bare MnO2 electrode. The SnO2 coating on MnO2 may be the cause of the enhanced charge and discharge capabilities of MnO2@SnO2.J. of Sci. and Tech. Res. 5(1): 83-92, 2023